Does the colonial past influence the model of tourism development? The case of Ehden (Lebanon) - Zakhia, Sally; Pérez-Pérez, Belén (Revista de Estudios Andaluces, 2024)
This research studies whether the tourism development model in Ehden (Lebanon) is sustainable and balanced, or whether, on the contrary, it responds to the unsustainable pattern of its colonial past. To this end, interviews with local stakeholders, surveys of residents and tourists were carried out and analysed using descriptive statistics and cross-sectional data techniques. The results show that local stakeholders want to promote an integrated tourism development model in Ehden based on territorial resources that involve the local population. The population is willing, for the most part, to get involved in the tourism development model of the town, and tourists are committed to diversified activities centred on the natural and cultural heritage of Ehden, which value the town’s specific resources. However, it has been detected that this is a demand of those with high income that stays in high quality hotels or rural accommodation and is concentrated in the summer months, which denotes a strong seasonality and unsustainability of tourism. It is concluded that, although the colonial past is present in the territory, there is currently a great interest from all the agents involved in tourism to promote an integrated tourism model that could help to boost economic diversification.